PENGARUH PENGELOLAAN LAPORAN KEUANGAN TERHADAP EFEKTIVITAS ARUS KAS PADA PT. MABAR MITRA BERSAMA - Clarissa W Manawan; M. Iqbal (Worksheet : Jurnal Akuntansi, 2021)
Cash flow is the basis for financial calculations and the management of financialstatements carried out by the company and its routine activities. Improper financialstatement management and unstable income and expenditure streams will result in acrisis for the company in the future. The effectiveness of cash flow is a measure of theextent to which the success of cash flow has an impact on the achievement andconsideration of the consequences that will be received by the company. The purpose ofthis study was to determine whether the management of financial statements owned byPT. Mabar Mitra Bersama affects the effectiveness of cash flow. The population of thisstudy are 42 employees of PT. Mabar Mitra Bersama where 30 employees of the financedepartment are the sample in this study. Simple linear regression test is a data analysistechnique used by the author in this study with the type of data used in the form ofquantitative data collected from respondents who filled out questionnaires. Based on theresults of the research that has been done, the value of the financial statementmanagement variable has a significance smaller than the probability value of 0.05, or thevalue of 0.000 <0.05, then Ha is accepted, H0 is rejected. Variable X has a t arithmeticvalue (21.935) greater than t table (2.048) so it can be concluded that the managementof financial statements has a significant influence on the effectiveness of cash flows andit can be seen that the contribution of financial management in influencing theeffectiveness of cash flows is 94 .5% while other variables only affect 5.5%.